Verification processes undertaken by mobile financial services (bKash) during pandemic situation in order to know their customers - Chowdhury, Jawad Mahmud (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.